Vocational High School Students' Satisfaction With Guidance and Counseling Services: A Comprehensive Survey - Rahmawati, Dhea Fitri; Laila, Farikha Nur; Salsabila, Vinensia Diana; Bariyyah, Khairul; Widiawati, Nanik (Proceedings Series of Educational Studies, 2024)
Student satisfaction is a crucial aspect of guidance and counseling services that affects students' positive or negative perceptions of these services. This study aims to identify the level of student satisfaction with guidance and counseling services in schools as a benchmark for improving service quality. This research uses a descriptive design with a survey method. Data were collected through questionnaires distributed online using Google Forms to all Grade X and XI students at SMK Muhammadiyah 3 Singosari. The research sample consisted of 57 students from various majors. The data obtained were analyzed using descriptive quantitative techniques. The results of the analysis showed that the average level of student satisfaction with guidance and counseling services was 73.67%. The majority of students reported dissatisfaction with the services due to an inadequate number of guidance and counseling teachers. Ideally, one guidance and counseling teacher should serve a maximum of 150 students. Although there are no specific hours for guidance and counseling due to adjustments to the Independent Curriculum, stricter supervision from the school is still needed so that guidance and counseling services can run optimally.